Childbirth injuries encountered on outreach in remote RDCongo - Lussy, Justin Paluku; Kitambala, Esther Kahambu; Mukekulu, Eugénie Kamabu (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This paper describes childbirth injuries encountered in remote DR Congo. Causes of identified injuries and their surgical repair outcomes are outlined. Methods: Through community awareness activities, patients with urinary or fecal incontinence were mobilized to report for care. Records from patients examined during outreach surgical camps in the Nord-Ubangi province from January to June 2018 were reviewed. Results: A total of 151 patients, ages 16-72 years, were attended for urinary and/or fecal incontinence after childbirth. Among 105patients who reported with urinary incontinence, 103 had vesico-vaginal fistulae that were classified as type I or type II (77 (77/103, 74.8%) patients) and type III of Waaldjik (26 (25.2%) patients). Two patients had urinary incontinence secondary to a small bladder.Among 46 patients who came complaining of fecal incontinence, 15 (15/46, 32.6%) patients had recto-vaginal fistulae while 31 (31/46, 67.4%) patients had third or fourth degree perineal tears. Vaginal delivery (79.2%), caesarean section (16.1%) and hysterectomy (4.7%) caused observed injuries.84.2% of the urinary incontinence group and 86.7% of the fecal incontinence group were dry and continent after repair. Conclusions: Genito-urinary fistulae were predominant among childbirth injuries encountered in remote DRCongo. Vaginal delivery was the leading cause of childbirth injuries. Surgical repair success rates were high.